The Korean Memorial Monument and the Recall of the Past in the Myanmar Area - Chotisut, Kridsana; Surakitbovorn, Siwat (Thai Journal of East Asian Studies, 2019)
The assassination attempt on South Korean leader by North Korean agents in 1983 in Yangon had an impact on relations of the countries on the Korean peninsula and Myanmar. After the incident, the narrative of martyrdom for the victims has been constructed by the South Korean government. The incident was reproduced through dramas by Korean private sectors. The political and economic reform of Myanmar and the severance of diplomatic relations between Myanmar and North Korea led to the investment, human resource development and economic assistance from the South Korea. South Korea proposed to establish a memorial for the victims in Rangoon and obtain approval from the Myanmar government. Opposition occurred as the construction site is where Myanmar honor their martyrs. However, as the monument did not impact the Myanmar Martyrs’ Mausoleum, a memorial monument for Korean victims was erected in Myanmar capital. The monument inauguration ceremony was associated with South Korea’s Memorial Day and the ceremonies were held every year to mark anniversary of the deadly bombing. This is a process of cross-border revisiting the past. This memorial monument has shifted from a place for Korean victims to the representation of the friendship between South Korea and Myanmar through both government representative’s address.